Determinants and Constraints for Adoption of Zero Budget Natural Farming (ZBNF) Practices - Kumar, Sunil; Nain, Manjeet Singh; Sangeetha, V; Satyapriya, (Indian Journal of Extension Education, 2023)
Zero Budget Natural Farming (ZBNF) follows agroecological principles and promotes chemical-free farming. It has emerged as cost-effective farming improving soil fertility and providing chemical-free food. For determining factors for the adoption of ZBNF practices in the purposively selected Wardha district of Maharashtra, conducted during 2022-23, Logit regression and for analyzing the constraints, factor analysis was used. The study revealed significant factors like integrated soil fertility management practices, adoption of ZBNF practices and IPM practices. The scarce raw materials for input preparation, management of weeds and pests were identified as input related whereas, lack of knowledge about liquid fertilizers, insect pest and weed management practices were reported as technology constraints, in case of the constraints related to labour and machinery, non availability of the bullock, high demand of skilled labour and high labour wages were reported. In case of institutional constraints, higher conversion period, high demand of skilled labour, and high certification fee were found. The assurance of better prices, purchase agencies at distant places, and lack of proper market structure were reported as the marketing constraints. In the case of political and legal constraints, a lesser number of FPOs, the synergy of the ZBNF practices with mainstream agriculture, lack of globalized market, and the need for convergence were found significant.
Keywords: Zero budget natural farming; Farmer field school; Logit regression; Constraints; Factor analysis